Quantitative and Qualitative Losses Inflicted by Caryedon serratus in Stored Groundnut Pods - Sundria, Man Mohan; Kumar, Akhil; Ahuja, D B (Annals of Arid Zone, 2016)
Studies on the qualitative and quantitative losses inflicted by C. serratus in stored groundnut pod during three to nine months of storage under fluctuating laboratory conditions revealed that pod weight loss (from 2.23 to 27.39%) and seed damage (from 29.52 to 96.02%) increased due to multiplication of bruchid population with the period of storage. Storage period coupled with insect infestation play vital role in decreasing the protein and carbohydrate (total soluble sugar) contents and in increasing oil content in the pods. Key words: Groundnut, Caryedon serratus, qualitative losses, quantitative losses.